Impact of ABO blood type on outcomes in patients with primary nonmuscle invasive bladder cancer - Klatte, Tobias; Xylinas, Evanguelos; Rieken, Malte; Kluth, Luis A; Rouprêt, Morgan; Pycha, Armin; Fajkovic, Harun; Seitz, Christian; Karakiewicz, Pierre I; Lotan, Yair; Babjuk, Marko; de Martino, Michela; et al. (The Journal of urology, 2014)
PURPOSE: ABO blood type is an established prognostic factor for several malignancies but its role in bladder urothelial carcinoma is largely unknown. We determined whether ABO blood type is associated with the outcome of transurethral resection of nonmuscle invasive bladder urothelial carcinoma. MATERIALS AND METHODS: We retrospectively studied ABO blood types in 931 patients with primary nonmuscle invasive bladder urothelial carcinoma treated with transurethral bladder resection with or without intravesical instillation therapy. Disease recurrence and progression were analyzed with univariable and multivariable competing risks regression models. Median followup was 67 months. Discrimination was evaluated by the concordance index. RESULTS: The ABO blood type was O, A, B and AB in 414 (44.5%), 360 (38.7%), 103 (11.1%) and 54 patients (5.8%), respectively. ABO blood type was significantly associated with outcome on univariable and multivariable analysis. Overall, patients with blood type O had worse recurrence and progression rates than those with A (p = 0.015 and 0.031) or B (p = 0.004 and 0.075, respectively). The concordance index of multivariable base models increased after including ABO blood type. CONCLUSIONS: In patients with nonmuscle invasive bladder urothelial carcinoma the ABO blood type may predict the outcome. Those with blood type O showed the highest recurrence and progression rates. Including ABO blood type in multivariable models increases the accuracy of standard prognostic factors. Since the ABO blood type is available for most patients, it may represent an ideal adjunctive marker to predict recurrence and progression. The biological explanation and prognostic value of this finding must be further elucidated.
Keywords: Cohort Studies; Retrospective Studies; karcinom z přechodných buněk; výsledek terapie; retrospektivní studie; Humans; kohortové studie; lokální recidiva nádoru; nádory močového měchýře; lidé; ABO Blood-Group System; progrese nemoci; Neoplasm Invasiveness; Carcinoma, Transitional Cell; Treatment Outcome; Urinary Bladder Neoplasms; invazivní růst nádoru; Disease Progression; Neoplasm Recurrence, Local; ABO systém krevních skupin